(untitled) (Journal of Nepal Geological Society, 2001)
The basin-fill sediment of the Kathmandu Valley is one of the best archives of both Himalayan uplift and past monsoon climate. Thick lacustrine sediments, mainly comprised of black clay, locally called as Kalimati clay, are the deposits of the Paleo-Kathmandu Lake during the last 2.5 million years, and the underlying fluvial sediments represent the deposits by the Proto-Bagmati River of the valley. The clay-predominant Kalimati Formation is rich in proxies of paleoclimate, such as fossil pollen and diatom as well as vertebrate and invertebrate fossils. In addition, crystallinity, chemical composition and stable isotope of clay minerals have a potential to provide a continuous paleoclimatic and paleoenvironmental records in the Central Himalaya. The sedimentological study of the fluvial and deltaic deposits that rest on the Kalimati Formation would reveal recent changes of tectonic and depositional environments in the Central Himalaya.